The development of umrah booking system / Amirah Aimi Zulkiflee - Zulkiflee, Amirah Aimi (2017)
Umrah Booking System is the system that is developed to help admin, staff and customer to manage Umrah booking through KRS Travel Sdn Bhd. The aim of this project is to develop an Umrah Booking System for KRS Travel Sdn Bhd. This project has three objectives that has been achieve which include gather and analyze the requirement, design and develop the Umrah Booking System. There were few problems encountered with manual Umrah booking process which leads to data redundancy and a lot of paper usage. It also consumes time to check on the seat availability. Besides, the current booking process leads to difficulties for the staff to keep track of the payment made by the customers. Mainly, this system focuses on Umrah booking. It also allows both staff and customer to check on seat availability of each package. Receipt of the payment also can be generate from this system. The methodology used for this system is Waterfall Model. This project involved four phases that begin with knowledge acquisition, requirement gathering and analysis, system design and system development. The programming language used for this system is JAVA language. As for the database, the author used SQL Developer to store the system‘s data. The future enhancement that can be made for this project is to enlarge the scope for other travels and can notify customer on the payment. To summarize, Umrah Booking System was developed from manual booking to online booking to reduce the current problem of Umrah booking process.